Mixing work with pleasure my life at Studio Ghibli - Suzuki, Toshio 1948 August 19-; Speares, Roger (Tokyo Japan Publishing Industry Foundation for Culture, 2018)
"Toshio Suzuki has devoted himself to Studio Ghibli for some thirty years, producing such world-renowned animated classics as "Princess Mononoke" and "Spirited away." Early in his career he met the two genius directors Hayao Miyazaki and Isao Takahata and gained their confidence. Working with these two inimitable directors, he experiences the joys and sorrows of filmmaking, and he continues today to guide the studio. Based on his innate inquisitive nature and the accumulated resources of thirty years, Suzuki has recounted in this book the story not only of Miyazaki and Takahata but also the other figures working at Studio Ghibli or in connection with it"--Dust jacket.
Preface to the English edition -- Preface to the revised Japanese edition -- About the Japanese revised edition -- In place of a preface: memories never to be forgotten -- 1. Mixing work with pleasure / trust means total trust: the animage era -- 2. The importance of shared interests in relationships: meeting Isao Takahata and Hayao Miyazaki -- 3. The importance of being the director's ally: Nausicaä of the Valley of the Wind and the founding of Studio Ghibli -- 4. New ideas are within a radius of three meters: Hayao Miyazaki filmmaking -- 5. Filmmaking is like tumbling all together down a slope: the philosophy and practice of Isao Takahata -- 6. There is no end to worrying in this world: the life of Yasuyoshi Tokuma -- 7. For making things, small companies are best: Ghibli as a "small neighborhood factory" -- 8. The future opens up to the steady and steadfast: always think in the present tense -- Afterword to the original Japanese edition (2008): how films result from casual conversation -- Afterword to the revised Japanese edition (2014): a word about flowers -- Toshio Suzuki chronology -- Bibliography.
Colophon also in Japanese.
Translation of: Shigoto dōraku; originally published by Iwanami Shoten in 2014.
Includes bibliographical references (pages 233-234).
Keywords: Suzuki, Toshio -- 1948 August 19- -- Friends and associates; Sutajio Jiburi, Kabushiki Kaisha; Motion picture producers and directors -- Japan -- Biography; Motion picture producers and directors -- Japan -- Anecdotes; Animated films -- Japan -- Anecdotes